The Influence of Digital Banking Through Self-Service Technology on Customer Satisfaction of Indonesian Islamic Banks - Salsabila, Tasya; Daulay, Aqwa Naser; Syarvina, Wahyu (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
Self-service technology (SST), including automated teller machines (ATMs), mobile banking services, and online banking, has made digital banking a popular trend that enhances the effectiveness and convenience of financial transactions. This study aims to determine how digital banking using SST affects customer satisfaction at Bank Syariah Indonesia, specifically among UIN SU Islamic banking students. The research adopts a quantitative methodology, involving a sample of 90 respondents from UIN SU. Data was gathered by distributing questionnaires via the WhatsApp application. The data analysis was performed using SmartPLS Version 4.0 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The findings indicated that digital banking has a positive and significant impact on customer satisfaction at Bank Syariah Indonesia, particularly among UIN SU students. Furthermore, digital banking also positively and significantly influences the implementation of Self-Service Technology (SST) in banking, which in turn positively and significantly affects customer satisfaction.